2019
DOI: 10.22190/fuvam1901031j
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Music Preferences Between Musicians and Non-Musicians

Abstract: The aim of this research was to check potential differences in music preferences between musicians and non-musicians. Music preferences were evinced by a short test on the topic (STOMP-R: Rentfrow & Gosling 2003), of the four types of music: Reflexive and Complex, Intense and Rebellious, Upbeat and Conventional, Energetic and Rhythmic. A sample of 209 students from the University of Niš (M=75; F=134), 112 non-musicians and 97 of musicians, were asked to give their opinion. The results of the t-test showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Furthermore, the more musically sophisticated their participants, the more able they were to dissociate roughness from pleasantness in classical and jazz chords. We also found that mean ratings for these genres were greater for musicians than for non-musicians ( Table 1 ), supporting previous research [ 29 ]. If we speculate that those musicians who reported a preference for classical, blues, folk and jazz also prefer to play these genres, our results might suggest that playing certain genres makes musicians more likely to report preference for higher complexity chords (please note that we were unable to test effect of genres played due to the small group sizes in our study).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the more musically sophisticated their participants, the more able they were to dissociate roughness from pleasantness in classical and jazz chords. We also found that mean ratings for these genres were greater for musicians than for non-musicians ( Table 1 ), supporting previous research [ 29 ]. If we speculate that those musicians who reported a preference for classical, blues, folk and jazz also prefer to play these genres, our results might suggest that playing certain genres makes musicians more likely to report preference for higher complexity chords (please note that we were unable to test effect of genres played due to the small group sizes in our study).…”
Section: Discussionsupporting
confidence: 90%
“…Both GoldMSI measures were included, to investigate whether formal training or more general musical engagement affects the response. From the STOMP, we tested the measure of preference for classical, blues, folk and jazz, since it has been shown to increase for musicians [ 29 ]. From the BMRQ, we included ‘Music Seeking’ and ‘Emotional Evocation’, since these have been shown to differentiate musicians and non-musicians in the past [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, previous findings show that the music preferences of both musicians and non-musicians vary only in a few music genres, such as classical and jazz music, which are preferred by musicians [57]. However, considering music taste on a whole level, not referring to any specific genre, both musicians and non-musicians exhibit a preference for consonant intervals, clear timbre, tonal structure, and regular rhythms [58]. This trend seems to be culturally influenced, as Amazonian natives show indifference toward dissonance sounds [59].…”
Section: Discussionmentioning
confidence: 96%